Investigating Teachers' Attitudes Toward Task-Based Language Teaching in a Vocational School in the UAE - Jasim, Imad Abdulkareem (2011)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Imad Abdulkareem Jasim entitled, "Investigating Teachers' Attitudes Toward Task-Based Language Teaching in a Vocational School in the UAE," submitted in June 2011. Available are both hard and soft copies of the thesis.